Cost burden of post-transplant lymphoproliferative disease following kidney transplants in Medicare-eligible patients by survival status. (1st January 2021) - Hart, Allyson; Ahn, Yoon Son; Watson, Crystal; Skeans, Melissa; Barlev, Arie; Thompson, Bryn; Dharnidharka, Vikas R.
Abstract: Aims and Objectives: Patients diagnosed with post-transplant lymphoproliferative disease (PTLD) experience high mortality within the first 2 years of diagnosis; however, few data exist on the economic burden of PTLD in these patients. We determined the healthcare resource utilization (HRU) and cost burden of post-kidney transplant PTLD and evaluated how these differ by survival status. Materials and Methods: Utilizing data from the United States Renal Data System and the Scientific Registry of Transplant Recipients, we identified 83, 818 Medicare-covered kidney transplant recipients between 2007 and 2016, of which 347 had at least one Medicare claim during the first year after diagnosis of PTLD. We tabulated Medicare Part A and Part B and calculated per patient-year (PPY) costs. Results: Patients diagnosed with PTLD in the first year post-transplant had Part A + B costs of 222, 336 PPY, in contrast with 83, 546 PPY in all kidney transplants. Post-transplant costs in the first year of PTLD diagnosis were similar regardless of the year of diagnosis. Cost burden for PTLD patients who died within 2 years of diagnosis was >3.3 times higher than PTLD patients still alive after 2 years. Of those who died within 2 years, the majority died within 6 months and costs were highest for these patients, with almost 7 times higher costs than PTLD patients who were still alive after 2 years. Limitations: Medicare costs were the only costs examined in this study and may not be representative of other costs incurred, nor be generalizable to other insured populations. Patients were only Medicare eligible for 3 years after transplant unless aged ≥62 years, therefore any costs after this cut-off were not included. Conclusions: PTLD represents a considerable HRU and cost burden following kidney transplant, and the burden is most pronounced in patients who die within 6 months.